13th ACM Web Science Conference 2021 2021
DOI: 10.1145/3447535.3462506
|View full text |Cite
|
Sign up to set email alerts
|

Is this a click towards diversity? Explaining when and why news users make diverse choices

Abstract: Modelling the different factors that lead people to choose news articles is one of the key challenges for understanding the diversity of news diets -as a news diet is the result of a series of decisions for certain articles over others, a sequence of choices that was made by the individual consumer. This study sheds light on the interplay between content-related (past behavior, habits, preferences) and situational factors (positioning, saturation, control). The latter could offer possibilities to promote more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Kravčík, Schmid, and Igel (2019) consider (cognitive) skills and affective responses of students in e-learning systems, while also laying out the importance of adapting intelligent mentoring systems to the user “based on ethnic diversity, cultural self-perception, preferences” (p. 21). Users can also be diverse in their “situational contexts” such as “location, time and role” (Lakehal et al 2018), their relationships to other users in a social network (Sanz-Cruzado and Castells 2018), and—coming full circle—their preferences for diversity in recommendations (Loecherbach et al 2021).…”
Section: Diversity Concepts In Cs and Technology Developmentmentioning
confidence: 99%
“…Kravčík, Schmid, and Igel (2019) consider (cognitive) skills and affective responses of students in e-learning systems, while also laying out the importance of adapting intelligent mentoring systems to the user “based on ethnic diversity, cultural self-perception, preferences” (p. 21). Users can also be diverse in their “situational contexts” such as “location, time and role” (Lakehal et al 2018), their relationships to other users in a social network (Sanz-Cruzado and Castells 2018), and—coming full circle—their preferences for diversity in recommendations (Loecherbach et al 2021).…”
Section: Diversity Concepts In Cs and Technology Developmentmentioning
confidence: 99%
“…News selections in NRSs depend not only on when and why readers seek out news but also on how they are presented. For example, Loecherbach et al (2021) showed that positioning can increase selection likelihood by up to 23%. This aligns with a larger body of research into recommender systems, which points to order effects that influence the perception and selection of choices (see Jesse and Jannach, 2021).…”
Section: Theoretically Informing Diversity Nudgesmentioning
confidence: 99%
“…This aligns with a larger body of research into recommender systems, which points to order effects that influence the perception and selection of choices (see Jesse and Jannach, 2021). Theoretical explanations for order effects range from habitual behaviours (Loecherbach et al, 2021) or primacy effects (Tintarev, 2017) to the perceived importance of prominently positioned items (Groot Kormelink and Costera Meijer, 2020).…”
Section: Theoretically Informing Diversity Nudgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Within communication science, scholars are increasingly reconsidering how recommender systems should be developed and how they can be used for purposes that support news organisations in their normative role of informing the public (Fields et al, 2018;Jones & Jones, 2019;Van den Bulck & Moe, 2018). A prominent idea in this discussion is the idea of so-called diversity-based news recommenders, also called diversity-enhancing news recommenders or diversity-oriented news recommenders (Bodó, 2019;Loecherbach et al, 2021). In contrast to other news recommender systems, the ultimate goal of these systems is not to provide individuals with more of the same news but to achieve diversity within individuals' news exposure behaviour.…”
Section: Diversity-based News Recommendersmentioning
confidence: 99%